A Complete Form of Pachydermoperiostosis Accompanied by a Pituitary Microadenoma - Chen YJ; Li L (Dove Medical Press, 2023)
Yan Jing Chen, Li Li Department of Dermatology and Venereology, West China Hospital, Sichuan University, Chengdu, Sichuan, People's Republic of ChinaCorrespondence: Li Li, Department of dermatology and venereology, West China Hospital, Sichuan University, Guoxue Alley No. 37, Wuhou District, Chengdu, Sichuan, 610041, People's Republic of China, Tel +86 18980601692, Email lilihx_scu@scu.edu.cnAbstract: Pachydermoperiostosis is a rare genetic disease that is associated with HPGD (15-hydroxyprostaglandin dehydrogenase) and SLCO2A1 (solute carrier organic anion transporter family member 2A1) gene mutations. It is characterized by three major phenotypes, namely, pachydermia, periostosis, and digital clubbing. Clinically, misdiagnoses such as acromegaly and thyroid acropachy are commonly confused with pachydermoperiostosis. Integral medical history, physical examination, endocrinological tests, and multiple disciplinary cooperation are extremely significant in the accurate diagnosis of pachydermoperiostosis. The co-existence of pachydermoperiostosis and pituitary adenoma is rarely recorded and discussed. In this case, we present a young male patient with a complete form of pachydermoperiostosis and a nonfunctional pituitary microadenoma, which has rarely been reported.Keywords: pachydermoperiostosis, pituitary microadenoma, acromegaly, thyroid acropachy